2004
DOI: 10.1080/0963818032000138206
|View full text |Cite
|
Sign up to set email alerts
|

The effect of revised IAS 14 on segment reporting by IAS companies

Abstract: International Accounting Standard (IAS) 14 on segment reporting was revised in 1997. IAS 14R substantially changed segment reporting requirements in response to numerous criticisms of the original standard. The objective of this study is to determine how IAS 14R affected the segment disclosure practices of companies claiming to comply with IAS. This paper examines the following questions: (1) What items of information are disclosed under IAS 14 and IAS 14R? Was there a gain or a loss of information disclosed f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
46
0
3

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(62 citation statements)
references
References 7 publications
11
46
0
3
Order By: Relevance
“…Meek and Gray (1989) also suggest that foreign stock exchange listing is likely to create an additional demand for disclosure, especially if the disclosure is mandatory or common in the foreign market. Findings in Mitchell et al (1995) and Prather‐Kinsey and Meek (2004) confirm the positive relation. Recall that the new standard is based on the US standard SFAS 131 and it is possible that many of the respondents have already adopted the new standard through their US foreign exchange listing.…”
Section: Hypothesis Developmentsupporting
confidence: 64%
See 1 more Smart Citation
“…Meek and Gray (1989) also suggest that foreign stock exchange listing is likely to create an additional demand for disclosure, especially if the disclosure is mandatory or common in the foreign market. Findings in Mitchell et al (1995) and Prather‐Kinsey and Meek (2004) confirm the positive relation. Recall that the new standard is based on the US standard SFAS 131 and it is possible that many of the respondents have already adopted the new standard through their US foreign exchange listing.…”
Section: Hypothesis Developmentsupporting
confidence: 64%
“…Because political visibility is higher for larger companies, they should be more supportive of ED 8, which mandates increased segment disclosure. Additionally, lower information production and proprietary costs (Meek et al 1995; Prather‐Kinsey and Meek 2004), and ownership dispersion (Prencipe 2004) inherent in large firms also justify the significant positive coefficient on size.…”
Section: Analysis and Resultsmentioning
confidence: 99%
“…In this view, previous studies on the topic showed that these costs might be due to two aspects (Prencipe, 2004, Prather-Kinsey andMeek, 2004;PisanoLandriana, 2012). The first is the technical complexity of defining the operating segment and identifying the transfer prices and allocate assets, liabilities and overheads amongst the different segments, especially when the reported segments do not correspond to internal organizational divisions (Mautz, 1968;Boersema and Van Weelden, 1992;Epstein and Mirza, 1998).…”
Section: International Journal Of Accounting and Financial Reportingmentioning
confidence: 99%
“…In our understanding, this is consistent with the substantial continuity of the use of the management approach. Previous studies (Street at al., 2000;Street and Nichols, 2002;Berger and Hann, 2003;Prather-Kinsey and Meek, 2004), in fact, proved that there was an increase in the number of reported segments when the accounting standard only requires to move from a risk-return approach (SFAS 14 and IAS 14) to a management approach, or in its complete version (SFAS 131), or in a hybrid version followed by IAS 14R (management approach with risk and rewards safety net). Differently, in the transition from the IAS 14R to IFRS 8, we see a substantial continuity of approach that does not imply a relevant increase in the number of the reportable segments but merely a higher discretion in the definition of the operative segments than shown in the past.…”
Section: What Are the New Segment Disclosure Characteristics Before Amentioning
confidence: 99%
See 1 more Smart Citation